Hubungan Gaya Belajar dengan Hasil Belajar Mata Kuliah Asuhan Kegawatdaruratan Maternal Neonatal Mahasiswa Tingkat II di Akademi Kebidanan Sari Mulia - Meyska Widyandini; Anggrita Sari; Mambang Mambang (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2019)
Midwifery education aims to establish an individual who have a good moral, quality, competent, and skill that are expected to be useful for society. The variety of students learning styles had to be known at the first moment they accepted in an educational institution. The suitability between learning styles and learning outcome will affect students success in learning. The research method used in this study was correlation method with cross sectional approach. The sample was the second grade students of Sari Mulia Midwifery Academy Banjarmasin which consisted of 67 students. The sample was taken by using simple random sampling technique. The instrument used in this study was checklist. The data analyzed were processed by using Chi Square test with significant standard α = 0,1. Through Chi Square analyzed, it found that the significant value of correlation between learning styles and learning outcomes of the students of Maternal Neonatal Emergency Care Course was 0,139 which is bigger than significant value obtained 0,1. It means, there is no correlation between learning styles and learning outcomes of Maternal Neonatal Emergency Care Course for the second grade students of Sari Mulia Midwifery Academy Banjarmasin. Based on the result of the study, it can be concluded that most of the respondent consisted of 31 students or (46,3%) dominantly used kinesthetic learning styles, and the students who got B or the greatest number learning outcomes of maternal neonatal emergency care course consisted of 29 respondent or 43,3%. Therefore, there is no correlation between learning styles and learning outcomes of Maternal Neonatal Emergency Care Course for the second grade students of Sari Mulia Midwifery Academy Banjarmasin.